Automatic detection of 39 fundus diseases and conditions in retinal photographs using deep neural networks - Ling-Ping Cen (Nature Portfolio, 2021)
Systems for automatic detection of a single disease may miss other important conditions. Here, the authors show a deep learning platform can detect 39 common retinal diseases and conditions.